ChemInform Abstract: Symmetry Reduction Due to Gallium Substitution in the Garnet Li6.43(2)Ga0.52(3)La2.67 (4)Zr2O12. Issue 19 (21st April 2016) - Robben, Lars; Merzlyakova, Elena; Heitjans, Paul; Gesing, Thorsten M.
Abstract: The title compound is obtained from stoichiometric amounts of La2 O3, ZrO2, Ga2 O3, and an excess of Li2 O (1323 K, 12 h).